ANALISIS PENGARUH GAYA KEPEMIMPINAN TERHADAP KEPUASAN KERJA, KOMITMEN ORGANISASI DAN KINERJA KARYAWAN (STUDI EMPIRIS PADA DEPARTEMEN AGAMA KABUPATEN KENDAL DAN DEPARTEMEN AGAMA KOTA SEMARANG) - Susilo Toto Raharjo; Durrotun Nafisah (JURNAL STUDI MANAJEMEN ORGANISASI, 2012)
ABSTRACT Path Goal theory explained about leader behavior by directive style, suportif style, partisipative style, maintenance style, and achievement style whice influence a wish. In order to influence low worker, by using one of four style, a leader must  effore to  influence perception and can give motivation to them about his duty clarity, attainment of target, job satisfaction and the effectively time. A leader take charge of to execute duty and also the such responsibility claimed [by] the existence of a leader recognizing as a whole the organizational member so that can grow harmonious same job among organizational component, here role of leader become of vital importance in efficacy of organization which leading of in the case of directive, supportif, partisipative and orient achievement for the job satisfaction, organizational commitmen and performance his subordinate. This research it all was done in Department Agama of Sub-Province of Kendal and Town Semarang, and it was taken example from staff office department agama of sub-province of Kendal and town Semarang. The technich which was used for research is giving 43 quesioner for depag Kendal and 90 depag Semarang, for measuringthese questions by scala likert.  The file for getting this research is helped by SPSS ( Statistical of Program of for Social Science) 7.5 for Windows. Analyse data is done by validity exam and reliabilitas exam by using Cronbach'S Alpha technic, correlation exam with “product moment technich” and regresi linear exam. It consisted of R² exam, F and t exam. The analysis which was  used is Chi-Square analysie to look for some  differences between depag Kendal and Semarang, and double regresi analyse influence of leadership style to job satisfaction, organizational commitmen, and the employees performance. The result of this research indicate that the five factors of leadership style : partisipative style, orient achievement style, directive style, supportif style, and maintenance style are have an effect on positively and signifikan to job satisfaction, organizational commitmen, and the employees performance. From this research results hope able to mange and consider the five variables as measure for developing job satisfaction, organizational commitmen and the employees performance. High and low of job satisfaction, organizational commitmen and the employees performance which was detaile from this research can be distinguished from  an influential leader, even it was believed that make a satisfield, commitmen, and the performance is not easy something and dependent, about a leadership generally tell about satisfaction, commitmen and officer performance can be followed from the leader, so one of superior leadership style. Is believed very suitable and determine job satisfaction, organizational commitmen and the employees performance from every organization Keyword : Leadership Style; Job Satisfaction; Organizational Commitmen; Employees Performance.